KAJIAN FONOLOGI METAFORA BAHASA DI WILAYAH PESISIR INDONESIA (PERSPEKTIF EKOLINGUISTIK) - Nisfatul Amaliya Nisfatul Amaliya (Prakata: Jurnal Bahasa dan Sastra Indonesia Serta Pembelajaran, 2026)
(This study explores the phonological aspects of metaphorical language in the coastal regions of Indonesia from an ecolinguistic perspective. The background of the research is rooted in the linguistic diversity of coastal areas, shaped by social, cultural, and geographical interactions. The objectives are to describe the phonological system of coastal languages, analyze phonological variations across regions, and identify social and geographical factors influencing the use of metaphors in coastal languages. The study employs a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. The findings reveal that coastal Indonesian languages exhibit flexible phonological patterns, a dominance of maritime vocabulary, and metaphorical expressions strongly related to the sea. Phonology plays a vital role in shaping metaphorical meanings, while the ecolinguistic perspective highlights the interconnection between language, culture, and the coastal environment. This research contributes to the preservation of local languages and enriches both theoretical and applied linguistics.